ChemInform Abstract: Concise Approach to Pyrrolizino[1, 2‐b]indoles from Indole‐Derived Donor—Acceptor Cyclopropanes. Issue 47 (3rd November 2016) - Villemson, Elena V.; Budynina, Ekaterina M.; Ivanova, Olga A.; Skvortsov, Dmitriy A.; Trushkov, Igor V.; Melnikov, Mikhail Ya.
Abstract: The ring opening of cyclopropanes (I) with sodium azide followed by Krapcho dealkoxycarbonylation and a subsequent Vilsmeier—Haack formylation of resulting azides (II) gives rise to azido aldehydes (IV).